Appropriateness of granulocyte colony-stimulating factor use in patients receiving chemotherapy by febrile neutropenia risk level. (October 2019) - Baig, Hassam; Somlo, Barbara; Eisen, Melissa; Stryker, Scott; Bensink, Mark; Morrow, Phuong K
Objective: Inappropriate granulocyte colony-stimulating factor use with myelosuppressive chemotherapy has been reported. Using the Oncology Services Comprehensive Electronic Records electronic medical record database, prophylactic granulocyte colony-stimulating factor (pegfilgrastim/filgrastim) use in cancer patients was assessed by febrile neutropenia risk level. Methods: Patients with nonmetastatic or metastatic breast, head/neck, colorectal, ovarian/gynecologic, lung cancer, or non-Hodgkin's lymphoma who received myelosuppressive chemotherapy from June 2013 to May 2014 were included. Prophylactic granulocyte colony-stimulating factor use with high-risk, intermediate-risk, and low-risk chemotherapy and distribution of National Comprehensive Cancer Network risk factors with intermediate-risk regimens were assessed. Results: Overall, 86, 189 patients received ∼4.2 million chemotherapy cycles (high risk, 9%; intermediate risk, 48%; low risk, 43%). Prophylactic granulocyte colony-stimulating factor was given in 24% of cycles (high risk, 59%; intermediate risk, 29%; low risk, 11%). For nonmetastatic solid tumors, granulocyte colony-stimulating factor was given in 78% (high risk), 31% (intermediate risk), and 6% (low risk) of cycles. For metastatic solid tumors or non-Hodgkin's lymphoma, granulocyte colony-stimulating factor was given in 50% (high risk), 27% (intermediate risk), and 11% (low risk) of cycles. Among patients receiving intermediate-risk regimens with granulocyte colony-stimulating factor, febrile neutropenia risk factors were identified in 56% (95% confidence interval, 51.1–60.9%) of patients with nonmetastatic solid tumors (n = 400) and in 70% (64.5–73.5%) of patients with metastatic solid tumors or non-Hodgkin's lymphoma (n = 400). Conclusion: Prophylactic granulocyte colony-stimulating factor use was appropriately highest for high-risk regimens and lowest for low-risk regimens yet still potentially underused in high risk regimens, overused in low-risk regimens, and not appropriately targeted in intermediate-risk regimens, indicating a need for further education on febrile neutropenia risk evaluation and appropriate granulocyte colony-stimulating factor use.